Oral Complications of Cancer Medication in Hemato-Oncologic Patients - Tariq Muhammad , Rasha; Fakhree Alzubaidee , Ali (Diyala Journal of Medicine, 2020)
Background: Chemotherapy is used to treat approximately 70% of cancer patients. Oral complications secondary to chemotherapy are recorded in about 80% of hemato–oncologic patients, these complications affect the patients’ quality of life and could sometimes be fatal. Objective: To describe the oral manifestations secondary to chemotherapy medication in hemato-oncologic patients and to determine which of those oral manifestations is more common. Patients and Methods: A sample of 190 patients presented to Nanakali Hospital for blood- related diseases and cancer in Erbil. The age range of the patients was 3-80 years, (mean 38.35 ± 22.62). Various types of malignancies, types of chemotherapy, and oral manifestation secondary to chemotherapy were recorded. Results: The most common type of cancer presented was leukemia (37.9%). In patients undergoing chemotherapy, the recorded oral manifestation was mucositis, xerostomia, fungal and viral infection. Mucositis was the most common, being recorded in 46.3% of the subjects. Conclusion: The results highlight the importance of the presence of a specialist in Oral and Maxillofacial Medicine working in coordination with the medical team to take care of the patients before, during and after chemotherapy. This multidisciplinary team can decrease the frequency of occurrence of oral manifestations, and can even assist in early diagnosis and management of oral lesions in case oral manifestation occurs.